Challenges to research implementation during public health emergencies: anecdote of insights and lessons learned during the COVID-19 pandemic in Gujarat, India - Memon, Farjana; Jobarteh, Modou L.; Shah, Komal; Sinha, Anish; Patel, Monali; Patil, Shailee; Heffernan, Claire; Saxena, Deepak B. (Frontiers in Public Health, 2024)
Health emergencies, including pandemics, are not new occurrences; some notable ones occurred in the past. However, the scale of the COVID-19 pandemic is unprecedented. The COVID-19 pandemic exposed the unpreparedness of national health systems in effectively managing health emergencies. During the pandemic, controlling the spread of the virus and hopes of exiting into a post-pandemic era were reliant on research to improve patient care and inform government policies. Nonetheless, research implementation during health emergencies can be challenging in low-resourced settings. This paper presents anecdotes of experiences and offers insight into ways research can be supported during health emergencies. We implemented a longitudinal study to investigate the impact of the COVID-19 pandemic, including SARS-CoV-2 infection, during pregnancy on maternal and child health outcomes. The study utilized hospital databases to recruit women who were infected and with no known SARS-CoV-2 infection during pregnancy. Mother-infant pairs in the infected and uninfected group were then followed longitudinally for 3 years. Observations, including challenges during planning, record retrieval, tracking, recruitment, and follow-up of eligible women, were reported by research staff. The challenges observed were group into three overarching themes: (a) individual factors, (b) health system challenges, and (c) research operational challenges. Some notable observations include misinformation, misconception, mistrust, underdeveloped health record systems, stigma, and hesitance. Early planning, effective communication, and community awareness can help in implementing a successful research project. Additionally, efforts to improve collaboration and co-creation between health practitioners, researchers, and the public may benefit the implementation of research projects during a health emergency.